PTU-135 Elaar (the Enhanced Liverpool Abdominal Area Ratio): How To Use Cross-sectional Imaging To Assess Prognosis In End-stage Cirrhosis. (9th June 2014) - Alam, SM; Farrell, C; Patanwala, I; Richardson, P; Cross, T
Abstract : Introduction: Liver size may be important in prognostication in cirrhosis. The LAAR score has previously shown a relationship between liver size and survival but is hampered by subjectivity. The current study aimed to improve the existing score. Methods: A retrospective-prospective cohort study was performed on patients with cirrhosis. The censor point used was date of patient death or liver transplant (LT) from CT date. Time points were measured from the date of the CT scan to censor point or last clinic appointment. The enhanced Liver pool to Abdomen Area Ratio (eLAAR) was derived using a software package (Carestream). eLAAR was calculated using the formula (Liver area (cm 2 )/Abdominal area (cm 2 ) x 100. Results: 101 patients were identified, 66% male, median age 52 (44–60 years). The LAAR score detected progression to death/LT in our cohort at 1 year (p = 0.02) and at 5 years (p = 0.03). The intra-class correlation coefficient between 2 operators was 0.94 (95% CI 0.89–0.97). Using an optimal eLAAR cut-off of 32 eLAAR could predict death at 1 and 5 years from diagnosis, p = 0.03 (OR 2.51(1.08–2.51) and p = 0.002 ()R 3.98 95% CI 1.5–10.4). Survival curves were constructed and the log rank test showed that eLAAR was able to predict death at 1 year (Log rank 5.3, p = 0.02) and 5 years (log-rank, p = 9.7, p = 0.002). Conclusion: The eLAAR score offers a new paradigm to identify patients with poor prognostic criteria on cross-sectional imaging who may benefit from liver transplantation. Disclosure of Interest: None Declared.